PC based home automation using universal serial bus - 413517 Hamdan Daniyal (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2002